The effect of nurses’ perceived social support on turnover intention: the chain mediation of occupational coping self-efficacy and depression - Liu, Zhenfan; Yan, Xiaoting; Xie, Guifang; Lu, Jing; Wang, Zhitong; Chen, Cui; Wu, Jijun; Qing, Wei (Frontiers in Public Health, 2025)
ObjectiveTo explore the chain mediating role of occupational coping self-efficacy and depression in the mechanism of nurses’ perceived social support on turnover intention.MethodsA convenience sample of 390 nurses from five general hospitals was surveyed from April–June 2024 using the General Information Questionnaire, the perceived social support scale, the occupational coping self-efficacy scale, the depression scale, and the turnover intention scale to construct and validate the chain mediated effects model.ResultsThe results of this study showed that nurses’ turnover intention scored (13.38 ± 4.83), perceived social support scored (70.25 ± 11.55), occupational coping self-efficacy scored (37.22 ± 5.45), and depression scored 6 (3.00, 11.00). The direct effect of perceived social support on nurses’ turnover intention their jobs was significant with an effect value of −0.1793; occupational coping self-efficacy and depression as separate mediating effects and chain mediating effects of both were − 0.0281, −0.0343, and − 0.0474, respectively.ConclusionNurses’ turnover intention is at a high level, and the chain-mediated effects of occupational coping self-efficacy and depression in the mechanism of nurses’ perceived social support on their turnover intention are established. Managers should pay attention to nurses with high turnover intention, increase their level of perceived social support, promote their occupational coping self-efficacy, and reduce their depression to further reduce their turnover intention and enable them to actively engage in their work.